Screening of novel narrow-spectrum benzofuroxan derivatives for the treatment of multidrug-resistant tuberculosis through in silico, in vitro, and in vivo approaches - Campos, Débora Leite; Canales, Christian Shleider Carnero; Demarqui, Fernanda Manaia; Fernandes, Guilherme F. S.; dos Santos, Camila Gonçalves; Prates, João Lucas B.; da Silva, Ingrid Gracielle Martins; Barros-Cordeiro, Karine Brenda; Báo, Sônia Nair; de Andrade, Leonardo Neves; Abichabki, Nathália; Zacharias, Luísa Vieira; et al. (Frontiers in Microbiology, 2024)
Tuberculosis remains a serious global health threat, exacerbated by the rise of resistant strains. This study investigates the potential of two benzofuroxan (Bfx) derivatives, 5n and 5b, as targeted treatments for MDR-TB using in silico, in vitro, and in vivo methodologies. In vitro analyses showed that Bfx compounds have significant activity against Mtb H37Rv, with Bfx 5n standing out with a MIC90 of 0.09 ± 0.04 µM.Additionally, their efficacy against MDR and pre-XDR strains was superior compared to commercial drugs. These Bfx compounds have a narrow spectrum for mycobacteria, which helps avoid dysbiosis of the gut microbiota, and they also exhibit high selectivity and low toxicity. Synergism studies indicate that Bfx derivatives could be combined with rifampicin to enhance treatment efficacy and reduce its duration. Scanning electron microscopy revealed severe damage to the morphology of Mtb following treatment with Bfx 5n, showing significant distortions in the bacillary structures. Whole-genome sequencing of the 5n-resistant isolate suggests resistance mechanisms mediated by the Rv1855c gene, supported by in silico studies. In vivo studies showed that the 5n compound reduced the pulmonary load by 3.0 log10 CFU/ml, demonstrating superiority over rifampicin, which achieved a reduction of 1.23 log10 CFU/ml. In conclusion, Bfx derivatives, especially 5n, effectively address resistant infections caused by Mtb, suggesting they could be a solid foundation for future therapeutic developments against MDR-TB.